KUALITAS LILIN AROMATERAPI DAN SABUN BERBAHAN MINYAK Dryobalanops aromatica - Gunawan Pasaribu; Gusmailina; R. Esa Pangersa G (BRIN Publishing, 2016)
The objective of this study was to determine the quality of aromatherapy candles and soaps that produced by the addition of Dryobalanops aromatica oil. Aromatherapy candles are made in several formulation variations, and then tested on 30 respondents to know the preference for candles. Parameters measured are prefereed for before candle burned, after burned and the perceived effects of aromatherapy. The soap is made in different formulations by adding Dryobalanops aromatica oil at 2, 4 and 6%, then tested the physico chemical properties. Results show that there are significant differencesof respondent preference between formulations before the candle is burned and formula with the lowest concentration of dryobalanop oil was most preferred. It does not indicate any preference difference between formulations after the candle is burned. However, the trend indicated that candle with medium oil concentration is more accepted. There were no significant differences in aromatherapical effects on various formulas. Aromatherapy candles formulation with the lowest concentration of dryobalanops oil is the most acceptable formulation that gives a positive effect on many respondents. Furthermore, the physico-chemical propertiesof the soap showed that water content and amountof fatty acids are below the standard limit, but the value of free fatty acid and saponified lipid levels could meet the ISO standards. Value of qualitative minerals content is negative. It was found that borneol compound as the Dryobalanops aromatica identifier in the form of endo borneol. The other encountered chemical compounds are caryophylene, alpha pinene, alpha humulene, alpha terpineol and dl-Limonene.